Apoptosis-triggered decline in hippocampal microglia mediates adolescent intermittent alcohol exposure-induced depression-like behaviors in mice. (15th June 2020) - Hu, Peili; Wang, Dan; Zhang, Yaru; Cai, Zixuan; Ye, Ting; Tong, Lijuan; Xu, Xing; Lu, Jiashu; Liu, Fengguo; Lu, Xu; Huang, Chao
Abstract: Depression-alcohol addiction comorbidity is a common clinical phenomenon. Alcohol exposure in adolescence has been shown to induce depression-like behaviors in rodents. However, the mechanism of action for this type of depression remains unclear. Previous studies have reported that several different types of stress, such as chronic unpredictable stress and early social isolation, trigger depression-like symptoms in mice by inducing hippocampal microglial decline, which is mediated by the initial activation of the microglial cells. Since alcohol also activates microglia, we evaluated the dynamic changes in hippocampal microglia in mice receiving adolescent intermittent alcohol exposure (AIE). Our results showed that 14 days of AIE, followed by 21 days period of no treatment, induced behavioral abnormalities as well as a significant loss and dystrophy of hippocampal microglia in mice. We found that this AIE-induced decline in hippocampal microglia was mediated by both microglial activation and apoptosis, as (i) 1 day of alcohol exposure induced a distinct activation of hippocampal microglia followed by their apoptosis, and (ii) blocking the initial activation of hippocampal microglia by pretreatment with minocycline suppressed the AIE-induced apoptosis and loss of hippocampal microglia as well as the AIE-induced depression-like symptoms. Lipopolysaccharide (LPS), a classical activator of microglia, ameliorated the AIE-induced depression-like symptoms by reversing the decline in the hippocampal microglia. These results reveal a possible mechanism for AIE-induced depression and demonstrate that the restoration of hippocampal microglial homeostasis may be a therapeutic strategy for depression induced by alcohol intake and withdrawal. Highlights: AIE induces a significant loss and dystrophy of microglia in hippocampal DG. Short-term alcohol exposure triggers microglial activation and apoptosis. Microglial apoptosis mediates AIE-induced loss of microglia in hippocampal DG. Microglial activation reverses AIE-induced depressive-like behaviors in mice.